Effect of volcanic eruption on nutrients, light, and phytoplankton in oligotrophic lakes - Modenutti, Beatriz Estela (2013)
Volcanic eruptions that shape the earth's surface can have major effect on ecosystems and, as natural experiments, can yield insights into ecological dynamics. On 04 June 2011, a mega-eruption in the Puyehue volcanic complex (Chile) discharged massive amounts of ash and pumice. Using long-term data from five North Andean Patagonian lakes (Espejo, Correntoso, Nahuel Huapi, Gutiérrez, and Mascardi) that received differing levels of ash, we show that, in Lakes Espejo, Correntoso, and Nahuel Huapi, these inputs resulted in 1.5- to 8-fold increases in total suspended solids, light extinction, phosphorus concentrations, and phytoplankton biomass relative to pre-eruption conditions. Although ashes affected light scattering, the ultraviolet : photosynthetically active radiation ratio remained ∼ 0.30–0.35 in all the lakes and no changes were seen in dissolved organic carbon in the affected lakes post-eruption. Thus, no differential specific absorption of the different light wavelengths occurred due to ash input. The results of multiple regression analysis identified light extinction coefficient of PAR (KPAR) as the primary variable that was associated with variation in phytoplankton biomass (chlorophyll). Furthermore, incubation experiments demonstrated significant effects of photoinhibition on phytoplankton growth in these lakes at ambient pre-eruption light intensities. Thus, we infer that increased phytoplankton biomass following the eruption likely reflects nutrient (phosphorus) loading and attenuation of excessive light intensities.